ISOLATION, OPTIMIZATION, AND ANTITUMOR ACTIVITY OF L-ASPARAGINASE EXTRACTED FROM PECTOBACTERIUM CAROTOVORUM AND SERRATIA MARCESCENS ON HUMAN BREAST ADENOCARCINOMA AND HUMAN HEPATOCELLULAR CARCINOMA CANCER CELL LINES - ABDEL-RAZIK, NOHA E; EL-BAGHDADY, KHALED Z; EL-SHATOURY, EINAS H; G MOHAMED, NAHLA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The objective of this research was to obtain isolates capable of producing a high yield of L-asparaginase enzyme and to evaluate the antitumor activity of the purified enzyme against different cancer and normal cell lines. Methods: Isolation of bacteria was performed by the serial dilution technique of soil samples collected from Cairo, Egypt, using modified M9 agar plates. Culture filtrates of selected isolates were quantitatively screened for L-asparaginase production using well-diffusion and direct nesslerization techniques. Factors influencing L-asparaginase activity were optimized by studying the effect of physical and nutritional conditions on the enzyme activity. The purification of L-asparaginase extracted from both the isolates was achieved using chilled acetone (−20°C), followed by gel filtration on Sephadex G-100. The anticancer activity of the purified enzyme against human breast adenocarcinoma (MCF-7), human hepatocellular carcinoma (HepGII) and homo sapiens human (WISH) cell line was examined by 3-(4,5-dimethylthiazol-2-yl)-2,5 diphenyl tetrazolium bromide assay. Results: Two L-asparaginase producers were identified by Biolog identification system as Pectobacterium carotovorum and Serratia marcescens. Optimization increased the production of L-asparaginase to 4.835 and 5.221 U/ml for P. carotovorum and S. marcescens, respectively. L-asparaginase was extracted, purified, and tested in vitro for cytotoxic activity using 3-(4,5-Dimethylthiazol-2-yl)-2,5 diphenyl tetrazolium bromide (MTT assay) against MCF-7, HepGII, and WISH cell line. L-asparaginase from P. carotovorum and S. marcescens was neutral to normal epithelial WISH cells. On the other hand, L-asparaginase from both isolates was cytotoxic to MCF-7 and HepGII cancer cell lines with an half maximal inhibitory concentration of 15 μg/ml and 26 μg/ml and 26 μg/ml and 25 μg/ml, respectively. Conclusion: L-asparaginase extracted from P. carotovorum and S. marcescens showed remarkable anticancer activity. Further studies on hypersensitivity action need to be carried out to recommend the use of L-asparaginase as an alternative to commercially available preparations.